Pyrenocine A induces monopolar spindle formation and suppresses proliferation of cancer cells. Issue 23 (1st December 2019) - Myobatake, Yusuke; Kamisuki, Shinji; Tsukuda, Senko; Higashi, Tsunehito; Chinen, Takumi; Takemoto, Kenji; Hachisuka, Masami; Suzuki, Yuka; Takei, Maya; Tsurukawa, Yukine; Maekawa, Hiroaki; Takeuchi, Toshifumi; et al.
Graphical abstract: Abstract: Pyrenocine A, a phytotoxin, was found to exhibit cytotoxicity against cancer cells with an IC50 value of 2.6–12.9 μM. Live cell imaging analysis revealed that pyrenocine A arrested HeLa cells at the M phase with characteristic ring-shaped chromosomes. Furthermore, as a result of immunofluorescence staining analysis, we found that pyrenocine A resulted in the formation of monopolar spindles in HeLa cells. Monopolar spindles are known to be induced by inhibitors of the kinesin motor protein Eg5 such as monastrol and STLC. Monastrol and STLC induce monopolar spindle formation and M phase arrest via inhibition of the ATPase activity of Eg5. Interestingly, our data revealed that pyrenocine A had no effect on the ATPase activity of Eg5 in vitro, which suggested the compound induces a monopolar spindle by an unknown mechanism. Structure-activity relationship analysis indicates that the enone structure of pyrenocine A is likely to be important for its cytotoxicity. An alkyne-tagged analog of pyrenocine A was synthesized and suppressed proliferation of HeLa cells with an IC50 value of 2.3 μM. We concluded that pyrenocine A induced monopolar spindle formation by a novel mechanism other than direct inhibition of Eg5 motor activity, and the activity of pyrenocine A may suggest a new anticancer mechanism.